Data Protection, Security and Storage - Sara Correia-Hopkins (Routledge Handbook of Online Violent Extremism)
This chapter discusses a range of data protection and security issues that may need to be considered by online violent extremism researchers conducting empirical projects. Its first half focuses on data collection, examining issues of lawfulness (in terms of both criminal and civil law), fairness and transparency. The second half considers safeguards that might be implemented, specifically confidentiality and de-identification, and data minimisation and security. Overall, the chapter emphasises the importance of a reflexive approach in which issues of research ethics are assessed on a case-by-case basis.